PENGARUH PENDIDIKAN DAN PENGALAMAN KERJA TERHADAP KOMITMEN ORGANISASI DAN PRESTASI KERJA PADA ANGGOTA SATUAN POLISI PAMONG PRAJA KOTA DENPASAR - Jayanti, A.A. Sg. Siskarini; Supartha, I Wayan Gede; Subudi, Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.11.TAHUN 2016, 2016)
Data collected through interviews, observation, and questionnaires. The study population was a civil servant at the Civil Service Police Unit Member of Denpasar. Samples taken in startified random sampling as much as 81 respondents. The analysis technique used to answer the problem of this research is the technique of path analysis with SPSS for Window 21. The results of this study indicate that 1) the education variable positive and significant effect on the variable organizational commitment; 2) variable work experience positive and significant effect on organizational commitment; 3) organizational commitment variable and not significant positive effect on job performance; 4) education variable positive and significant effect on work performance and 5) variable work experience and significant positive effect on work performance.
Keywords: education, work experience, organizational commitment and job performance